2017
DOI: 10.2490/prm.20170015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for In-hospital Mortality and Reamputation Following Lower Limb Amputation

Abstract: Objective: Studies on the outcomes of lower limb amputation have been limited by the use of selected study populations and small sample sizes. Although reamputation is an important outcome following lower limb amputation, the risk factors for reamputation remain to be elucidated. The present study was performed to identify risk factors for in-hospital death and reamputation following lower limb amputation. Methods: Using a national inpatient database in Japan, we identified 13,774 patients who underwent lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…Mann-Whitney U-test, t-test, and χ2 test were used to compare background characteristics and indices of physical function between the two groups with re-amputation histories versus groups with no reamputation histories, depending on the data characteristics. Multivariate Cox regression analysis was also performed after adjusting for confounders by inputting sex [2], age [10], serum albumin levels [25], and knee extension muscle strength [26] as covariates with reference to items that were signi cant in univariate analysis and previous studies to identify factors associated with re-amputation. To account for multicollinearity in this process, variables considered clinically signi cant were left in the model if the absolute value of the correlation coe cients between the independent variables was greater than 0.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mann-Whitney U-test, t-test, and χ2 test were used to compare background characteristics and indices of physical function between the two groups with re-amputation histories versus groups with no reamputation histories, depending on the data characteristics. Multivariate Cox regression analysis was also performed after adjusting for confounders by inputting sex [2], age [10], serum albumin levels [25], and knee extension muscle strength [26] as covariates with reference to items that were signi cant in univariate analysis and previous studies to identify factors associated with re-amputation. To account for multicollinearity in this process, variables considered clinically signi cant were left in the model if the absolute value of the correlation coe cients between the independent variables was greater than 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of lower limb amputations in Japan, the amputation rate in the 1960s was 1.6/100,000 patients, and 70% of the amputations were caused by trauma; however, in the 2000s, the amputation rate was reported to be 5.8/100,000 patients, and the cause was peripheral circulatory disturbances in 66.2% of cases [1]. A prognostic study of amputee patients reported that the mean age of patients with foot amputations was 72.4 years and that the re-amputation rate was 18.2% [2].…”
Section: Introductionmentioning
confidence: 99%
“…A Mann-Whitney's U-test, t-test, and χ2 test were used to compare background factors and indices of physical functioning between the two groups with reamputation histories versus groups with no reamputation histories, depending on the data characteristics. Multivariate Cox regression analysis was also performed after adjusting for confounding by inputting sex [2], age [10], serum albumin levels [26], and knee extensor muscle strength [27] as covariates with reference to items that were signi cant in univariate analysis and previous studies to identify factors associated with reamputation. To account for multicollinearity in this process, variables that were considered clinically important were left in the model if the absolute value of the correlation coe cients between the independent variables was greater than 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of lower limb amputations in Japan, the amputation rate in the 1960s was 1.6/100,000 patients, and 70% of the amputations were caused by trauma; however, in the 2000s, the amputation rate was reported to be 5.8/100,000 patients, and the cause was peripheral circulatory disturbance in 66.2% cases [1]. A prognostic study of amputee patients reported that the mean age of patients with foot amputations was 72.4 years and that the reamputation rate was 18.2% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mann-Whitney U-test, t-test, and χ2 test were used to compare background characteristics and indices of physical function between the two groups with reamputation histories versus groups with no reamputation histories, depending on the data characteristics. Multivariate Cox regression analysis was also performed after adjusting for confounders by inputting sex [2], age [10], serum albumin levels [25], and knee extensor muscle strength [26] as covariates with reference to items that were signi cant in univariate analysis and previous studies to identify factors associated with reamputation. To account for multicollinearity in this process, variables that were considered clinically important were left in the model if the absolute value of the correlation coe cients between the independent variables was greater than 0.7.…”
Section: Discussionmentioning
confidence: 99%